Plaque Removal Efficacy of 3 Cleaning Methods for Removable Orthodontic Appliances: A Crossover Randomized Clinical Trial - Homa Farhadifard; Sepideh Soheilifar; Anahita Bakhshaei (Galenos Yayinevi, 2021)
Objective: The mechanical plaque removal methods for removable orthodontic appliances (ROAs) may damage the surface of the appliance and may not effectively eliminate the entire microbial plaque. This study aimed to compare the efficacy of brushing+denture cleansing tablets, brushing+propolis mouthwash, and brushing only, for plaque removal from the surface of each orthodontic appliance.Methods: This crossover randomized clinical trial evaluated 32 patients aged 7-15 years with ROAs. The patients were randomly assigned to 3 groups of brushing (control), brushing + denture cleansing tablets (intervention group 1), and brushing + propolis mouthwash (intervention group 2). The plaque removal methods were switched among the groups during 3 periods, each of 1-month duration. One month after practicing a certain protocol, the plaque disclosing agent was applied on the surface of the appliance. The photographs of the appliances were analyzed by Image J software to calculate the surface area occupied by the residual microbial plaque.Results: The ratio difference between the surface area of residual plaque to the surface area of the entire appliance was significant between the intervention group 1 and the control group (P < .001), while it was not significant between the intervention group 2 and the control group (P = 0.105). Moreover, this difference between the intervention groups 1 and 2 was statistically significant (P < .001).Conclusion: The simultaneous use of toothbrush with denture cleaning tablets decreased the microbial biofilm on the surface of ROAs to a better extent, compared to the results with brushing alone. Thus, it appears that the use of denture cleaning tablets may be suitable for effective cleaning of ROAs.